2016
DOI: 10.2147/dddt.s118461
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and evaluation of VEGF-siRNA/CRS as a novel vector for gene delivery

Abstract: Small interfering RNA (siRNA) delivery is a prospective method in gene therapy, but it has application limitations such as negative charge, water solubility and high molecular weight. In this study, a safe and efficient nano-vector, CRS, was designed and synthesized to facilitate siRNA delivery. Physical and chemical properties of VEGF-siRNA/CRS were characterized by methods including scanning electron microscopy (SEM), transmission electron microscopy, zeta potential (ζ) measurement, drug-releasing rate measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…These factors including positive surface charge and small particle size must have contributed to the increased transfection efficiency. Our results were supported by other studies indicating that the amount of positive charges on the cell surface and the size of the vector/oligonucleotide complex played important roles in determining successful gene delivery [4143]. A positively charged structure is desirable since it can preferentially adhere to the negatively charged cell surface receptors, leading to endocytosis.…”
Section: Discussionsupporting
confidence: 86%
“…These factors including positive surface charge and small particle size must have contributed to the increased transfection efficiency. Our results were supported by other studies indicating that the amount of positive charges on the cell surface and the size of the vector/oligonucleotide complex played important roles in determining successful gene delivery [4143]. A positively charged structure is desirable since it can preferentially adhere to the negatively charged cell surface receptors, leading to endocytosis.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, clinical attentions have been largely focused on anti-angiogenesis by inhibiting VEGF to achieve anti-tumor treatment . A number of studies have shown that small interfering RNA (siRNA) targeting VEGF (siVEGF) has great potential in the treatment of tumors by blocking VEGF genes. However, it is challenging to efficiently deliver siRNA to tumors via systemic administration, with the barriers including poor stability, low cellular uptake, endosomal degradation, and off-target effects.…”
Section: Introductionmentioning
confidence: 99%